The Impact of the Unavailability of the Cheque’s Issuance Date under the Jordanian Judiciary and Law of Commerce - AlNaser, Mohammed (DIRASAT: SHARI'A AND LAW SCIENCES, 2016)
The Jordanian Law of Commerce considers the cheque’s issuance date as an obligatory element in this paper which is considered an important instrument among negotiable instruments. However, the provisions of the Law of Commerce are vague when it comes to the effect of the unavailability of this obligatory element. On the one hand, the Law of Commerce considers that missing the date of issue results in not considering this instrument as a cheque, while on the other hand the law provides that the issuer of a cheque missing the date of issue is subject to being penalized with a fine, which means that the instrument is valid as a cheque along with the penalty provided in the law.In light of this legislative ambiguity, the decisions of the Jordanian Court of Cassation came to add contrdation to the said ambiguity. While the court considered the cheque missing the date of issue as a cheque, other decisions by the court considered that this instrument is not a cheque.The article presents its hypothesis based on the proposition that these instruments should be considered as cheques even if the date of issue is missing. In this context, the paper introduces a comprehensive solution based on the said hypothesis which is in line with the principles of negotiable instruments which require saving the interests of the holders thereof and encouraging them to accept and endorse these intruments. The solution took into consideration the case of presenting the cheque to the drawee (the bank) and to the courts, in addition to the case of the bankruptcy of the drawer.